The Hypothesis of the Unknowableness of Negatives - Kiedrowski, Krzysztof (Sensus Historiae, 2022)
The goal of this paper is the analysis and critique of the proof of the unknowableness of negatives present in negativistic unitarian metaphysics, formulated by Leszek Nowak in three volumes of Being and Thought. His conception aims, inter alia, at establishing a new concept of negativity. If the presented argument is valid, it will prove that Nowak's conception of negativity is not as profound and consequential as it was previously thought to be.